The Origins of Sarawak Malay: Tracking the Obscure Points: (Asal Usul Melayu Sarawak: Menjejaki Titik Tak Pasti) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2015)
Sarawak Malays are complex. The Malays are the result of various processes and the course of history and culture, including migration, assimilation and amalgamation. The objective of this article is to identify the origin of the Malays in Sarawak, Malaysia. There are four schools of thought about the origins of the Malays in Sarawak. Firstly, that, like the Malays in Brunei, Sabah, the Malay Peninsula, and the like, are actually indigenous or native to Sarawak, and not from other areas in the region. Secondly, is the belief that the Malays originated from the archipelago including Java and Sumatra. Thirdly, that they are from outside the archipelago, namely Arabs who assimilated with Malay tribes and other races. Fourthly, that they are other indigenous people from Sarawak who converted to Islam and experienced absolute assimilation. This is the group that is considered as "masuk Melayu" (become Malay), resulting in the extinction of some indigenous minorities. Despite the existence of the Malays native to Sarawak along with other indigenous ethnicities, some Sarawak Malays originate from elsewhere.Keywords: Sarawak Malays, Islam, assimilation, ethnic relations, indigenous